PILGRIMAGE: PHENOMENON OF PASSAGE - Kochappilly, Paulachan (Journal of Dharma, 2006)
The month of December is a special season of pilgrimages. As I reflect on the topic, Islamic pilgrimage, hajj, is held in full swing with religious piety and gaiety in Saudi Arabia having had worldwide preparation and highlevel organisation. Watching the scene in television is, indeed, spectacular and sacred, a moment of religious fulfilment for millions in white garb and a memorable movement of people around the stone in the holy city of Islam. It is food for senses to see great rivers of humanity flood into Arabia from every point of the compass overflowing the avenues of Mecca during the pilgrimage. The reason for such a mammoth gathering is obvious: “The holiest of all is in Mecca – there, in the centre of the sacred, forbidden city, is the terrestrial heart of Islam.”1 Pilgrimage, hajj, is something obligatory for every Muslim (as it is the fifth pillar of Islam), of course, who can afford the journey.2 “Night and day the dark-draped Ka’bah is the centre about which a vast, surging current of faithful perform the ritual circling, again surrounded, wave upon wave, by a sea of exhausted pilgrims lying upon the ground or seated or standing in attitudes of devotion and prayer.”3 At the same time, we watch the Indian media giving coverage to the scam on hajj. It is unfortunate to learn that the middlemen mismanage the money for a religious cause.